A novel treatment option in management of tubal ectopic pregnancy after in vitro fertilization with embryo transfer by trans-vaginal aspiration of gestational sac: a case report - Mishra, Vineet; Roy, Priyankur; Choudhary, Sumesh; Aggarwal, Rohina; Gandhi, Khushali; Saini, Suwa Ram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Majority of the reports suggest that the frequency of ectopic pregnancies have grown in the last 30 years, especially in patients conceived through artificial reproductive techniques (ART). Ectopic pregnancy occurs mostly in the fallopian tubes (90%), and the most common region is the ampula. Its prompt diagnosis and appropriate management is important in preventing severe morbidity and mortality. In a select patient population, most of the unruptured, live ectopic pregnancies can be successfully managed without surgical intervention using trans-vaginal ultrasound guided aspiration and instillation of local injection KCl or administration of systemic injection Methotrexate. We report a case of tubal ectopic pregnancy in a patient who underwent IVF-ET and was successfully treated conservatively by ectopic aspiration and instillation of injection KCl locally in the ectopic site.